Hydrogenation of organic matter as a terminal electron sink sustains high CO2:CH4 production ratios during anaerobic decomposition. (October 2017) - Wilson, Rachel M.; Tfaily, Malak M.; Rich, Virginia I.; Keller, Jason K.; Bridgham, Scott D.; Zalman, Cassandra Medvedeff; Meredith, Laura; Hanson, Paul J.; Hines, Mark; Pfeifer-Meister, Laurel; Saleska, Scott R.; Crill, Patrick; et al.
Highlights: Organic matter hydrogenation provides an electron sink during anaerobic decomposition. This mechanism sustains CO2 production and suppresses methanogenesis. Thus this mechanism controls climate feedbacks by altering CO2 :CH4 production ratios. Abstract: Once inorganic electron acceptors are depleted, organic matter in anoxic environments decomposes by hydrolysis, fermentation, and methanogenesis, requiring syntrophic interactions between microorganisms to achieve energetic favorability. In this classic anaerobic food chain, methanogenesis represents the terminal electron accepting (TEA) process, ultimately producing equimolar CO2 and CH4 for each molecule of organic matter degraded. However, CO2 :CH4 production in Sphagnum- derived, mineral-poor, cellulosic peat often substantially exceeds this 1:1 ratio, even in the absence of measureable inorganic TEAs. Since the oxidation state of C in both cellulose-derived organic matter and acetate is 0, and CO2 has an oxidation state of +4, if CH4 (oxidation state −4) is not produced in equal ratio, then some other compound(s) must balance CO2 production by receiving 4 electrons. Here we present evidence for ubiquitous hydrogenation of diverse unsaturated compounds that appear to serve as organic TEAs in peat, thereby providing the necessary electron balance to sustain CO2 :CH4  > 1. While organic electron acceptors have previously been proposed to drive microbial respiration of organic matter through the reversible reduction of quinone moieties, the hydrogenation mechanism that we propose, by contrast, reduces CC double bonds in organic matter thereby serving as (1) a terminal electron sink, (2) a mechanism for degrading complex unsaturated organic molecules, (3) a potential mechanism to regenerate electron-accepting quinones, and, in some cases, (4) a means to alleviate the toxicity of unsaturated aromatic acids. This mechanism for CO2 generation without concomitant CH4 production has the potential to regulate the global warming potential of peatlands by elevating CO2 :CH4 production ratios.